Contribution of the support leg to accelerate kicking leg swing during soccer instep kicking - Inoue, K.; Nunome, H.; Sterzing, T.; Sato, N.; Ikegami, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The present study aimed to determine the contribution of support leg motion to the acceleration of the kicking leg in soccer instep kicking. The kicking motion was recorded by a motion capture system. According to the procedures proposed in previous studies, the power due to the muscle and interaction moments acting on the kicking lower leg was computed. The forward swing of the lower leg during the final phase of kicking was dominated by the power of the interaction moment rather than by that of the muscle moment. The support leg motion contributed to produce more than 50 % of the total amount of positive work due to the power of the interaction moment. The present study proposed a reasonable mechanism for the acceleration of the lower leg swing when its angular velocity exceeds the inherent force-velocity limitation of muscles.